PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM BIMBINGAN KONSELING UNTUK MENINGKATKAN HASIL BELAJAR SISWA (Studi Kualitatif di SMK Negeri 1 Setu) - Abdul Mukhlis; Siti Asiah (Turats, 2020)
The role of Islamic religious education teachers in schools is not only teaching religious materialbut also Aas: informer, organizer, motivator, director, initiator, transmitter, facilitator, mediator,evaluator. So that teachers can know the needs of students and can guide students to develop theirpotential. The purpose of this study was to determine how the role of teachers in counseling guidanceto improve student learning outcomes in Islamic religious education subjects at SMK Negeri 1 Setu, aswell as to determine the supporting and inhibiting factors of the teacher’s role in counseling guidanceto improve student learning outcomes. This study uses a qualitative method naturalistic researchthat is based on the view of phenomena and seeks to understand the meaning of events and theirrelation to the object of research. From the results of this study, it can be seen that the role of Islamicreligious education teachers in counseling guidance at SMK Negeri 1 Setu is 1. Identifying studentswho need counseling guidance. 2. Coordinate with counseling guidance teachers. 3. Teach religiousmaterial. 4. Educate students to be good characters. 5. Helping students with problems get back onthe right path. With the role of Islamic religious education teachers in counseling guidance results inincreased learning outcomes. This can be seen from the spiritual value, the value of knowledge and thevalue of skills. The supporting factors for the teacher’s role in counseling guidance are: the existenceof cooperation between Islamic religious education teachers, homeroom teachers and parentsof students so that can make it easier to help develop student learning outcomes, the existence ofsupporting facilities and infrastructure, learning media used by teachers to make it easier for studentsto learn. While the inhibiting factors are: lack of communication between parents, especially in lawenforcement of school rules which causes misunderstandings, incomplete facilities and infrastructure,limited learning media, still doing 2 shifts in learning.